Analisis Penerimaan Pajak Bumi dan Bangunan (PBB) terhadap Pendapatan Daerah di Kecamatan Kotarih - Audi Fazhillah; Nurlaila Nurlaila (Jurnal Riset Akuntansi, 2024)
This research aims to analyze regional tax revenues on regional income in Kotarih sub- district. The data used in this research is a verbal question and answer process that takes place in one direction. The results of this research show a positive relationship between tax revenues and income in Kotarih sub-district, Serdang Bedagai district. Regional government income used to finance development comes from various sources, one of which is taxation. To finance the region and promote its development, it can adopt a tax revenue optimization policy in which everyone is obliged to pay taxes in accordance with their obligations and established legal rules. One of the potential regional taxes based on regional expenditure, the Serdang Bedagai Regency Government recorded a quite good increase in the funds involved. Increasing regional tax revenues will improve the welfare of urban communities by providing regional income by regulating the community's economy so that it can grow and develop.